IMPACT OF GLOBALIZATION ON CRITICAL INFRASTRUCTURE - JAKUBCZAK Weronika (2011)
Despite of the fact that creation of critical infrastructure was a result of globalization processes there are very few references to globalization while talking about it. The fight against present-day international terrorism caused by globalization leaded to recognition of infrastructure parts as strategic for every state. The necessity to select certain parts of from general national infrastructure and organize a system security for it became obvious. Thus it was recognized as “critical infrastructure” and the crisis management system based on national administration was created to protect it.